The influence of Hedonic Shopping Motivation, Shopping Lifestyle, and Shopping Enjoyment on Fashion Consumers' Impulse Purchases in e-Commerce - Fitriani, Desi Dwi; Auliya, Zakky Fahma (Profesional Muda Cendekia Publishing, 2023)
The purpose of this study is to analyze the effect of Hedonic Shopping Motivation, Shopping Lifestyle, and Shopping Enjoyment on the impulse purchases of fashion consumers on Shopee. The population in this study is consumers domiciled in Karanganyar Regency. The sample in this study is fashion consumers at Shopee who have used and are users of Shopee. The respondents used in this study numbered 120. Data was analyzed using IBM SPSS Statistic software version 26. This research method is quantitative research method. The data analysis method used is multiple linear regression analysis. The results showed that: (1) From the results of significant values of 0.329 > 0.05 and calculated values of 0.980 < table 1.658 so that it can be concluded that Hedonic Shopping Motivation (X1) has no effect on Impulse Buying (Y). (2) From the results of a significant value of 0.000 < 0.05 and a calculated value of 4.862 > table 1.658, it can be concluded that Shopping Lifestyle (X2) has a significant effect on Impulse Buying (Y). (3) From the results of significant values of 0.010 < 0.05 and calculated values of 2.625 > table 1.658 so that it can be concluded that Shopping Enjoyment (X3) has a significant effect on Impulse Purchases (Y). So it can be seen from the three independent variables above that Shopping Lifestyle is the most influential variable in this study, with the value of significance and calculated value.